LITERATURE, IMAGE AND RESISTANCE: THINGS FALL APART AND THE RESCUE OF ANCESTRAL MEMORIES - Chagas, Alessandra Santos (Sankofa (São Paulo), 2022)
This paper aims to investigate literature’s role in the representation of the relationship between the colonized and the colonizer from Chinua Achebe’s novel Things fall apart (2009); besides to study how this relationship changes the colonized society and its traditions. In order to do that, this work focused on the works of Bonnici (2005), Fanon (2008/1952), Santos (2008), Kilomba (2019) and Césaire (2020/1950); besides Achebe’s African Trilogy, as well as his critical works. Hence, it was observed that Achebe's literature is caracterized as a post-colonial writing and made it possible to change the image created by the colonial literary tradition, inaugurating a new way to write about Africa, considering the colonized’s point of view. Furthermore, Achebe enabled the emergence of positive identities as well as the valorization of ancestral memories.